Multiparameter measuring system using fiber optic sensors for hydraulic temperature, pressure and flow monitoring. (28th February 2022) - Liu, Mingyao; Wu, Yihang; Song, Han; Zou, Yao; Shu, Xianshuang
Highlights: A metal-coated fiber Bragg grating temperature sensor is proposed. A fiber Bragg grating flow sensor is proposed. A Fabry-Perot pressure sensor is proposed. A multiparameter measuring system consisting of the proposed sensors is developed. The performance of the proposed sensor and system is verified by experiments. Abstract: In this paper, based on the research of fiber optic sensing technology, a multiparameter measuring system for hydraulic parameter monitoring is developed and evaluated. The sensing theory, design, calibration, and installation of the proposed metal-coated fiber Bragg grating temperature sensor, fiber Bragg grating flow sensor, and Fabry-Perot pressure sensor are detailed in the paper. A special hydraulic platform is designed for system test and the parameter monitoring condition of the hydraulic platform is displayed by the graphical user interface designed by using LabVIEW. The effectiveness of the designed system is verified by analyzing and comparing the obtained data of electrical sensors and the proposed sensors installed in the hydraulic platform. Experimental results indicate that the designed system using fiber optic sensing technology can accurately detect the parameters of the hydraulic equipment, and can be potentially used for real-time detection for condition monitoring of hydraulic equipment by analyzing the characteristic parameters.